Wage bill change in Ireland during recession - how have employers reacted to the downturn - Walsh, Kieran (Statistical and Social Inquiry Society of Ireland, 2012)
The Earnings, Hours and Employment Costs Survey (EHECS) captures information each quarter on total earnings, paid hours and level of employment from a large representative sample of employers. Responses received typically cover more than 70% of all employees in the state. The main purpose of the survey is to gauge trends in the average level of earnings and hours worked over time across all sectors of the economy. However the presence of the same employers in the sample over time creates a valuable opportunity to undertake longitudinal analysis of the manner in which employers change their wage bill over time. A previously published study from EHECS comparing quarter 3 2008 with quarter 3 2009 showed that for the matched employers, covering over half of all employees in the state, nearly two thirds of those employers had cut their wage bill by more than 2 percent over the year with the primary method of reduction being a reduction in numbers employed, followed by reductions in hours worked and reductions in hourly rates of pay. The level and type of change differed significantly across sectors. This paper will present an update of the findings from that publication for the following years (covering 2009 to 2011) to assess how the behaviour of employers changed as the economic downturn continued.
read before the Society, 9 February 2012
Keywords: employment; earnings; nominal wage rigidity; wage bill reductions during recession; 314.15